NATO and the EU: Who has the main role in ensuring energy security in Europe? Instances of (de)securitization of energy security on part of NATO and the EU and their overlap in the protection of critical (energy) infrastructure - Atanasov, Dimitar Dimitrov (2023)
Energy security has been on the priority list of the European Union for a long time, but since the early 2000s, after the former eastern bloc countries joined NATO, the Alliance too has turned its gaze towards this topic. After the Russian annexation of Crimea at the beginning of 2014, there was a major shift in the geopolitical and security environments in Europe, and energy security climbed high on the lists of the EU and NATO, but both reacted differently towards it. After the beginning of the war in Ukraine on February 24, 2022, the EU and NATO started functioning in a new (in)security environment when it came to energy, which was reminiscent of 2014. Using Securitization Theory and the concept of Institutional Overlap, this work set out to find the answer to the question of what is the role of the EU and NATO in ensuring energy security in the new security framework in Europe, and which International Organization bears more responsibility to do so? After a thorough analysis of statements, documents, and press releases from both IOs, it was concluded that the EU carries more responsibility for ensuring the energy security on the Old Continent, mainly because it was proven that the Union securitizes security of supply much more than the Alliance between the trigger years of 2014 and 2022.